A prospective pilot study of intravitreal aflibercept for the treatment of chronic central serous chorioretinopathy: the CONTAIN study. Issue 6 (16th January 2015) - Pitcher, John D; Witkin, Andre J; DeCroos, Francis Char; Ho, Allen C
Abstract : Aim: To evaluate the role of intravitreal aflibercept injection as a treatment for eyes with chronic central serous chorioretinopathy (CSCR). Methods: This prospective pilot study enrolled 12 patients with chronic CSCR who received a 6-month treatment regimen of intravitreal aflibercept. Patients were followed with monthly Early Treatment of Diabetic Retinopathy Study (ETDRS) best-corrected visual acuity (BCVA) and spectral domain optical coherence tomography (SD-OCT) with enhanced depth imaging. Results: All patients were men between 29 and 64 years (median 55). Subfoveal fluid was present on OCT for a median duration of 6 months (range 4–29 months) prior to treatment. Baseline BCVA ranged from 20/25 to 20/160 (median 20/50) with a mean of 62 (SD=13) ETDRS letters. No patients experienced serious ocular or systemic adverse events over the course of the study. Post-treatment BCVA ranged from 20/20 to 20/200 (median 20/40), with a mean of 64 (SD=16) ETDRS letters (p=0.56). At baseline, three patients (25%) had BCVA of ≥20/40 versus seven patients (58%) at the conclusion of the study. Two patients gained at least 15 ETDRS letters and no patients lost more than 15 ETDRS letters. Six of 12 patients (50%) had complete resolution of subfoveal fluid. Mean central macular thickness decreased from 400 µm (SD=104 µm) to 306 µm (SD=94 µm) (p=0.03), and mean subfoveal fluid decreased from 159 µm (SD=93 µm) to 49 µm (SD=68 µm) (p=0.02). Mean choroidal thickness decreased from 307 µm (SD=72 µm) to 263 µm (SD=63 µm) (p=0.0003). Conclusions: Intravitreal aflibercept was well tolerated over a 6-month treatment course for chronic CSCR. No change was observed in visual acuity metrics. Anatomic trends may suggest some morphological activity, but larger controlled trials are needed. Trial registration number: NCT01710332